Characterization of the Gain Coefficient and Electroabsorption of an AlGaAs Quantum Well Sample - García Lara, Carlos; Vázquez, R.; Mendoza, S.; Camas, J. (Revista Cubana de Física; Vol 27 No 1 (2010), 2010)
We present the optical characterization of a photorefractive quantum well sample of AlGaAs with 1.645 µm thicknesses, using an automatic system of two wave mixing, particularly controlling a tuned laser diffraction grating from 835 a 850nm. Several characteristics were analyzed, the sample response at different wavelengths, power laser and, electric fields applied. We observed two absorption peaks, due to exciton present in the sample, at 838nm and 845nm respectively, with 2,4 and 6 applied voltage using a 4.7kΩ resistor and 50mA maxim current laser. Thus a great electro-absorption coefficient, due an electric field applied to a semiconductor change the material absorption, known like quantum Stark effect, observed in longitudinal configuration. Furthermore, using fringes separately by 1µm and a 4000 and 6000v/cm applied, we observed the best diffraction efficiency at 835nm where are located the upper excitonic peak.